PEMANFAATAN MEDIA SOSIAL DALAM MENGEMBANGKAN KEHARMONISAN PASANGAN SUAMI ISTRI DENGAN PROBLEM JARAK DAN WAKTU - Renatasari, Ribka Greta; Wijaya, Albert I Ketut Deni (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
This study examines how married couples facing distance and time-related challenges can maintain and develop harmony by utilizing social media. The study highlights the communication issues these couples face due to physical separation and how technological advancements, particularly social media, offer solutions. The aim is to explore the role of social media in fostering marital harmony in the context of distance and time problems. A qualitative research method was employed, with data collected through in-depth interviews. The study involved 11 participants, all of whom are married couples experiencing distance and time challenges. The findings reveal that social media plays a crucial role in bridging the communication gap between couples. Features such as video calls and photo sharing enable couples to stay connected and maintain intimacy despite the distance. The use of social media thus contributes significantly to the preservation and development of marital harmony.